BioGoldNCDB: A Database of Gold Nanoclusters and Related Nanoparticles with Biomedical Activity - Eszter Erdei; András Mándoki; Andrea Deák; Balázs Balogh; László Molnár; István M. Mándity (Molecules)
Interest in gold nanoclusters (AuNCs) has grown significantly in recent decades. AuNCs, with a core size smaller than 2 nm, represent a unique class of functional nanomaterials. Their distinctive properties enable innovative applications across various interdisciplinary fields. Here, we introduce BioGoldNCDB, a freely available, fully annotated, and manually curated database of mainly about AuNCs and related AuNPs. Despite the rapid growth in biomedical applications of gold nanoclusters (AuNCs), the lack of a centralized and structured data resource hinders comparative analysis and rational design. Researchers face challenges in accessing standardized information on AuNCs’ structures, properties, and biological activities, which limits data-driven development in this emerging field. The database provides essential information, including CAS numbers and PubMed IDs, as well as specific details such as biomedical applications, cell lines used in research, particle size, and excitation/emission wavelengths. It currently covers 247 articles from 104 journals. Designed with a user-friendly and intuitive web interface, BioGoldNCDB is accessible on multiple devices, including phones, tablets, and PCs. Users can refine searches with multiple filters, and a help page is available for guidance. While offering quick insights for newcomers, BioGoldNCDB also serves as a valuable resource for researchers across various fields.